Study on the Key Genes and Molecular Mechanisms of IL-27 Promoting Keratinocytes Proliferation Based on Transcriptome Sequencing - Wu Z; Yang Q; Xu K; Wu J; Yang B (Dove Medical Press, 2023)
Zijun Wu,1,2,* Qin Yang,3,* Kai Xu,2 Juanjuan Wu,2 Bin Yang1,2 1The First School of Clinical Medicine, Southern Medical University, Guangzhou, People's Republic of China; 2Department of Burn and Plastic Surgery, General Hospital of Central Theater Command, Wuhan, People's Republic of China; 3Department of Laboratory Medicine, General Hospital of Central Theater Command, Wuhan, People's Republic of China*These authors contributed equally to this workCorrespondence: Bin Yang, The First School of Clinical Medicine, Southern Medical University, Nos.1023-1063, Shatai South Road, Baiyun District, Guangzhou, Guangdong, 510515, People's Republic of China, Tel +86-18062601971, Email sszxkyb1@163.comBackground: IL-27 involves psoriasis pathogenesis potentially by promoting excessive keratinocyte proliferation. However, the underlying mechanisms remain unclear. This study aims to explore the key genes and molecular mechanisms of IL-27-induced keratinocyte proliferation.Methods: Primary keratinocytes and immortalized human keratinocyte HaCaT cells were treated with different concentrations of IL-27 for 24 h and 48 h respectively. CCK-8 assay was used to detect cell viability and Western blot was used to detect the expression of CyclinE and CyclinB1. Primary keratinocytes and HaCaT cells were treated with IL-27, and their differentially expressed (DE) genes were obtained by transcriptome sequencing. Then Kyoto Encyclopedia of Genes and Genomes enrichment analysis was performed to predict related pathways, and the long non-coding RNA-microRNA-messenger RNA network and protein-protein interaction network were constructed to screen key genes. Biochemical experiments were performed to assess the content of glucose (Glu), lactic acid (LA), and ATP. Flow cytometry and Mito-Tracker Green staining were used to detect mitochondrial membrane potential and the number of mitochondria respectively. Western blot was performed to assess the expression of glucose transporter 1 (GLUT1), hexokinase 2 (HK2), lactate dehydrogenase A (LDHA), phosphoglycerate kinase 1 (PGK1), phosphorylated dynamin-related protein 1 (p-DRP1) (s637) and mitofusin 2 (MFN2).Results: IL-27 concentration-dependently increased keratinocyte viability and the expression of CyclinE and CyclinB1. Bioinformatics analysis showed that the enriched pathways of DE genes were closely associated with cellular metabolism. miR-7-5p, EGFR, PRKCB, PLCB1 and CALM3 were key genes. IL-27 increased the content of LA, mitochondrial membrane potential, and the expression of GLUT1, HK2, LDHA, PGK1, p-DRP1 (s637), and MFN2, accompanied by decreased contents of Glu and ATP (P< 0.001).Conclusion: IL-27 potentially promotes keratinocyte proliferation by enhancing glycolysis, mitochondrial function, and mitochondrial fusion. The findings of this study may be conducive to revealing the role of IL-27 in the pathogenesis of psoriasis.Keywords: psoriasis, RNA-seq, glycolysis, mitochondria